Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Biologi Kelas XIA di SMAN 1 Bunobogu - Fadila, Nurul; Lilies, Lilies; Jamhari, Mohammad; Bialangi, Mursito; Windarsih, Yulia; Binti Non Shamdas, Gamar (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to improve student learning outcomes in Biology through the implementation of Project Based Learning (PBL) in class XIA at SMAN I Bunobogu. The method used in this study is a Classroom Action Research (CAR) design consisting of four stages: planning, implementation, teacher observation, and student observation. The subjects of this study were 28 students in class XIA. The data collection instruments used in this study included teacher observation sheets, student observation sheets, and post-tests. The results of this study indicate that the project-based learning model in Biology has significantly improved student learning outcomes. This is demonstrated by the data analysis conducted during the first cycle, which showed a student learning outcome rate of 71%, while the second cycle saw an increase to 93%. Based on the results of this study, it can be concluded that the implementation of the Project-Based Learning model successfully improved student learning outcomes.